Detection of Acanthamoeba spp. using carboxylesterase antibody and its usage for diagnosing Acanthamoeba-keratitis. - Min-Jeong Kim; Ki-Back Chu; Hae-Ahm Lee; Fu-Shi Quan; Hyun-Hee Kong; Eun-Kyung Moon (PLoS ONE)
Contact lens usage has contributed to increased incidence rates of Acanthamoeba keratitis (AK), a serious corneal infection that can lead to blindness. Since symptoms associated with AK closely resemble those incurred by bacterial or fungal keratitis, developing a diagnostic method enabling rapid detection with a high degree of Acanthamoeba-specificity would be beneficial. Here, we produced a polyclonal antibody targeting the carboxylesterase (CE) superfamily protein secreted by the pathogenic Acanthamoeba and evaluated its diagnostic potential. Western blot analysis revealed that the CE antibody specifically interacts with the cell lysates and conditioned media of pathogenic Acanthamoeba, which were not observed from the cell lysates and conditioned media of human corneal epithelial (HCE) cells, Fusarium solani, Staphylococcus aureus, and Pseudomonas aeruginosa. High titers of A. castellanii-specific antibody production were confirmed sera of immunized mice via ELISA, and these antibodies were capable of detecting A. castellanii from the cell lysates and their conditioned media. The specificity of the CE antibody was further confirmed on A. castellanii trophozoites and cysts co-cultured with HCE cells, F. solani, S. aureus, and P. aeruginosa using immunocytochemistry. Additionally, the CE antibody produced in this study successfully interacted with 7 different Acanthamoeba species. Our findings demonstrate that the polyclonal CE antibody specifically detects multiple species belong to the genus Acanthamoeba, thus highlighting its potential as AK diagnostic tool.